Representaciones sociales sobre el estrés y sus efectos en la salud de docentes y funcionarios de una institución educativa privada de la cuidad de Tunja (2022)
The general objective of this research work was to know the social representations about stress and its effects on health. The study was structured under descriptive qualitative research, where different categories involving subcategories were analyzed. Its importance was centered on the interpretation given to the concept of work stress, in order to offer an integral vision of it in the field of teachers' performance towards the effects on their mental health.